Analisis Jaringan Bisnis Terhadap Perusahaan Saiber.Id Sebagai E-Commerce Yang Bergerak di Bidang Fashion - Qoulan Karima; Muhamad Ramdan; Resya Dwi Marselina; Rosa Amelia (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
An extensive business network can have an impact on the operations of a business. Retail business in Indonesia in general is the activity of selling various goods or services. Saiber.id operates in the economic sector. There are many benefits that entrepreneurs can obtain through networking. For example, increasing sales, marketing strategies, increasing relationships and acquaintances, self-development, and much more. From the results of the research we have carried out, the results obtained regarding the analysis of the Saiber.id company can be concluded that: The Saiber.id company is an E-commerce company that has been operating in the fashion sector since 2017. The Saiber.id company produces its products starting from glondongan to products that are ready to be sold, according to Saiber.id there are differences from when it was first established until now, in the past The development of E-commerce has not been as rapid as it is now and this has affected sales, along with current technological advances making it easier for consumers to access using online platforms. For the business network carried out by saiber.id, following several seminars and introducing their products to colleagues or close friends, saiber.id also collaborates with two raw material providers in the Padalarang lanun, apart from that, saiber.id carries out endorsements for branding. to make their products more famous and familiar to the target market they are looking for.